The Healthy Minds, Thriving Kids Project: Educator perspectives on relevance and potential impact of a mental health skill building program. - David Anderson; Jeffrey Chapman; Janine Domingues; Gabriella Bobadilla; Mimi Corcoran; Harold Koplewicz (PLoS ONE)
Background Healthy Minds Thriving Kids (HMTK) is a free to user mental health skill building program developed by the Child Mind Institute with the aim to normalize conversations about emotional health and provide educators with wellness tools. The aim of this study was to explore the applicability of the HMTK program for universal school-based delivery from the perspective of educators, specifically to understand acceptability of program materials, perception of the quality of the program, and impressions of the program's usefulness and relevance across K-12 settings. Methods The HMTK program was available to view by educator registrants between 01/26/2022 and 09/07/2022 in the State of California. Educator participants viewed an introductory video for the program and a minimum of two skills videos before participating in an online survey. Results Of 68,861 registrants to the website, 64,376 provided survey data. Post-pandemic levels of stress and anxiety were increased, and 89.5% of respondents said young people required a greater degree of support than in the past. Almost all educators (90%) endorsed a need for additional mental health skill building tools for students, and following review of HMTK, > 80% of respondents said they would use the program in their classrooms. Most (86.6%) found the program engaging, and 85.1% found the program relevant to and representative of their student cohorts. More than three quarters (79.6%) said their students would find the program engaging and beneficial. Post-exposure to HMTK, 18.8% more educators believed that the State of California was committed to supporting students' emotional learning. Conclusion This survey demonstrates that from the perspective of educators the HMTK program is a valuable and complementary resource to school curricula to improve the mental health skills of young people. It provides an easy-to-implement framework that school districts and administrators can integrate within their curriculum planning.